Inpatient Dermatology (Springer International Publishing, 2018)
Inpatient Dermatology is a concise and portable resource that synthesizes the most essential material to help physicians with recognition, differential diagnosis, work-up, and treatment of dermatologic issues in the hospitalized patient. Complete with hundreds of clinical and pathologic images, this volume is both an inpatient dermatology atlas and a practical guide to day-one, initial work-up, and management plan for common and rare skin diseases that occur in the inpatient setting. Each chapter is a bulleted, easy-to-read reference that focuses on one specific inpatient dermatologic condition, with carefully curated clinical photographs and corresponding histopathologic images to aid readers in developing clinical-pathologic correlation for the dermatologic diseases encountered in the hospital. Before each subsection the editors share diagnostic pearls, explaining their approach to these challenging conditions. This book is structured to be useful to physicians, residents, and medical students. It spans dermatology, emergency medicine, internal medicine, infectious disease, and rheumatology. Inpatient Dermatology is the go-to guide for hospital-based skin diseases, making even the most complex inpatient dermatologic issues approachable and understandable for any clinician. .